2016
DOI: 10.1038/srep34673
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution 3D volumetry versus conventional measuring techniques for the assessment of experimental lymphedema in the mouse hindlimb

Abstract: Secondary lymphedema is a common complication of cancer treatment characterized by chronic limb swelling with interstitial inflammation. The rodent hindlimb is a widely used model for the evaluation of novel lymphedema treatments. However, the assessment of limb volume in small animals is challenging. Recently, high-resolution three-dimensional (3D) imaging modalities have been introduced for rodent limb volumetry. In the present study we evaluated the validity of microcomputed tomography (μCT), magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…We have also included how good positioning affects interrater agreement compared to poor positioning, and we examined the intrarater agreement. Frueh et al had shown that the interrater agreement was high (r = 0.975, p < 0.001) for µCT analysis 17 . Their BA LoA where a lot wider than ours when examining the interrater agreement.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We have also included how good positioning affects interrater agreement compared to poor positioning, and we examined the intrarater agreement. Frueh et al had shown that the interrater agreement was high (r = 0.975, p < 0.001) for µCT analysis 17 . Their BA LoA where a lot wider than ours when examining the interrater agreement.…”
Section: Discussionmentioning
confidence: 98%
“…The population of interest consisted of C57BL/6 mice from two prior experiments, and the rater population of interest was comprised of medical staff with a BSc degree. Interrater agreement for µCTanalysis has previously been shown to be high (r = 0.975, p < 0.001) 17 . While the study by Frueh et al focused on the comparison of µCT with several different measuring techniques, reporting additionally on interrater agreement, our study targeted intra-and interrater agreement in µCT measuring, and the Guidelines for Reporting Reliability and Agreement Studies (GRRAS) 22 were applied.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Caliper-measured paw thickness represents a valid surrogate parameter for rodent hindlimb volumes. 25 Repetitive measurements in isoflurane anesthesia were performed over a period of 14 weeks.…”
Section: Paw Thickness Measurementsmentioning
confidence: 99%